SPE Middle East Oil and Gas Show and Conference 2019
DOI: 10.2118/195036-ms
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Steel Casing: Detecting Zonal Isolation in the Borehole Environment

Abstract: Electrically resistive composite casing materials are being introduced to the oil & gas industry. Resistive casing enables electromagnetic logging for exploration and reservoir monitoring, but it requires development of new logging methods. Here we present a technique for the detection of integrity of magnetic cement behind resistive casing. We demonstrate that an optimized induction logging tool can detect small changes in the magnetic permeability of cement through a non-conductive casing in a vertical (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Oil and gas companies annually spend huge amounts of money to eliminate them, but the success rate of these works does not exceed 40% (Figure 1). The results of early studies [1,2,3] revealed the existence of effective technologies for solving this problem. However, the applicability of these results and products is limited by their cost and conditions of use, as only the payback of the proposed technologies requires an increase of oil production no less than 250 tons/day from each well, while in the conditions that are investigated in this work, the maximum level of oil production that the company produces from one well is no more than 5-6 tons/day.…”
Section: Introductionmentioning
confidence: 99%
“…Oil and gas companies annually spend huge amounts of money to eliminate them, but the success rate of these works does not exceed 40% (Figure 1). The results of early studies [1,2,3] revealed the existence of effective technologies for solving this problem. However, the applicability of these results and products is limited by their cost and conditions of use, as only the payback of the proposed technologies requires an increase of oil production no less than 250 tons/day from each well, while in the conditions that are investigated in this work, the maximum level of oil production that the company produces from one well is no more than 5-6 tons/day.…”
Section: Introductionmentioning
confidence: 99%
“…For GFRP we can assume 𝜇 = 𝜇 [20], and the range of the reflection wave coefficient is Modern turbine blades are often made of GFRP material with εr = 4.2, for which the reflectance is approx. 9 dB.…”
mentioning
confidence: 99%
“…To compare the RCS formula for Annex 2 with the formula for Annex 1 (13), we can convert the Equation (20) to…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of cement integrity is of primary importance to the oil and gas industry [9]. Poor cementation can lead to costly accidents and serious damage to the environment.…”
mentioning
confidence: 99%